Clinico-epidemiological profile and disease severity of chronic obstructive pulmonary disease among patients in a primary care centre at central Kerala - G. R., Sreelekshmi; A. J., Austoria; Raj, Ajitha; Mathew, Thushara (International Journal Of Community Medicine And Public Health, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is a chronic disease usually caused by significant exposure to noxious particles and are not fully reversible. COPD represents an important public health challenge that is both preventable and treatable. The aim of this study was to describe the clinico-epidemiological profile of COPD patients and to assess the disease severity using spirometry among respiratory symptomatic in a primary care centre. Methods: A cross sectional study was conducted among the COPD patients attending monthly pulmonology clinic in Urban Health centre, Ettumanoor, Kottayam from June to August 2019. The study comprised of 120 patients with symptoms suggestive of COPD attending the monthly respiratory clinic. Severity of airflow limitation assessed using spirometry results based on GOLD criteria. Clinical and epidemiological data were collected using a semi structured interview schedule. Results: The mean age of the participants were 64±12 and 51.7% were males. The median duration of COPD symptoms for the study participants was 10 (IQR 11) years and 62.5% were having productive cough with dyspnoea as the major symptom. All males except two were smokers and the mean packyears were 42±4 years. As per GOLD guidelines 44 (36.7%) had severe disease, 11 (9.2%) had mild, 39 (32.5%) had moderate and 26 (21.7%) had very severe disease. The average forced expiratory volume in one second (FEV1) in study subjects was 54.8±7.5. Conclusions: In view of the emerging public health risk, COPD need to be diagnosed and managed at the earliest to slow down the progression.